Design and fabrication of minimalzie wall table with storage / Wan Muhammad Jazli Na'im Wan Rozain - Wan Rozain, Wan Muhammad Jazli Na'im (2022)
The primary goal for this project is to design and fabrication the minimalize wall table with storage. The problems are there are too many people in the room that make the room narrow, no dining room in the room and the room is small. The reason chose the topic are it can save space, can be used more than 1 person in one time and simplify matters. The objectives are to design and fabricate minimalize wall table with storage. The methodology of doing this project are 3 ideas will be designed, an engineering drawing in Solidwork, material selection, cost estimation, fabrication and testing. The scope for this project are for student in the room and will use the available material in the lab. The contribution is helping student to have dining room in their room. The problem for this project the table space will be cramped as it filled with their learning items such as books, stationery and others. The objective of this project is to design and design the wall table with storage. For the scope of this project is the student and available material in lab.